Neurofinance and Investment Decisions in an Emerging Market: The Moderating Role of Financial Literacy - Yusuf, Muhammad; Naufal, Hanif Afif; Syaifullah, Muhammad Yusuf (Indonesian Journal of Accounting and Governance, 2025)
Investment decision-making in financial markets is increasingly recognized as a process shaped by both cognitive and neurobiological factors. While prior behavioral finance studies have extensively examined psychological biases, empirical evidence integrating neurofinance and financial literacy remains limited, particularly in emerging market contexts. This study investigates the influence of neurotransmitter-related traits on investment decisions, with financial literacy examined as a moderating mechanism. Using primary survey data from 412 retail investors in an emerging market, this study applies Partial Least Squares Structural Equation Modeling (PLS-SEM) to test a moderated structural model. Neurotransmitter traits are specified as a higher-order construct capturing reward sensitivity, emotional regulation, vigilance, and stress responsiveness. Financial literacy is modeled as a moderator using a two-stage interaction approach. The findings reveal that neurotransmitter traits exert a positive and statistically significant effect on investment decisions. Financial literacy also demonstrates a direct positive effect on investment decision-making. However, the moderation analysis indicates a negative and significant interaction effect, suggesting that higher levels of financial literacy attenuate the influence of neurobiological traits on investment decisions. This result supports the interpretation of financial literacy as a behavioral buffering mechanism, reducing reliance on instinctive or emotionally driven investment behavior. This study contributes to the behavioral finance and neurofinance literature by providing empirical evidence on the conditional role of financial literacy in shaping investment decisions within an emerging market. The findings offer practical implications for investor education policies and financial market development strategies aimed at fostering more informed and disciplined investment behavior.